1988
DOI: 10.2514/3.23057
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of an underexpanded rectangular jet ejector

Abstract: An experimental investigation was carried out on a rectangular ejector (constant area mixing duct) with an underexpanded rectangular jet as the primary flow. From the wall static pressure measurements, the ejector performance was found to show irregular variations with the primary jet pressure. Hot-wire measurements, together with schlieren photographs, showed that better performance was obtained when the flow was well mixed. The well-mixed flow was found when the screech tone Strouhal number was in the 0.11-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The velocity of the propagating vortex loop which is circular in nature is considerably less (U T x in Table II If the exit nozzle of the shock tube has an area comparable with the inlet of the ejector, it makes more effective usage of the principle operation of the ejector which is to entrain ambient air. The large spreading of the jet leads to better mixing, a statement in agreement with the findings of Hsia et al 23 The entrained air increases the momentum of the flow and hence the impulse created at the ejector exit. Figure 18 shows a selection of the schlieren photographs which express the main components of the flow created at the exit of the ejector.…”
Section: Flow Structures Generated At the Ejector Exitsupporting
confidence: 90%
“…The velocity of the propagating vortex loop which is circular in nature is considerably less (U T x in Table II If the exit nozzle of the shock tube has an area comparable with the inlet of the ejector, it makes more effective usage of the principle operation of the ejector which is to entrain ambient air. The large spreading of the jet leads to better mixing, a statement in agreement with the findings of Hsia et al 23 The entrained air increases the momentum of the flow and hence the impulse created at the ejector exit. Figure 18 shows a selection of the schlieren photographs which express the main components of the flow created at the exit of the ejector.…”
Section: Flow Structures Generated At the Ejector Exitsupporting
confidence: 90%
“…The under expanded flow fields concerns the under-expanded primary flow: at the nozzle's exit plane, the primary flow pressure is higher than that of the secondary flow and the so called 'shock train' (a succession of oblique and/or nor-mal shock waves) occurs. When considering the flow fields in a rectangular shape ejector, the interested reader may also refer to the study of Little et al [1], Hsia et al [47] and Koite et al [48].…”
Section: Ejector Efficiency Evaluation Proceduresmentioning
confidence: 99%
“…For this area ratio and for underexpanded conditions, the C Pf values for the multiple jet ejector are lower, indicating a better performance. The irregular behavior of C P[ for a single jet ejector is a result of acoustic interactions inside the duct, the details of which are described by Hsia et al 2 It was also found that, for subsonic conditions, i.e., for R < 1.9, the difference in the data for single and multiple jet ejectors at corresponding conditions are insignifi-J. PROPULSION VOL.…”
Section: A Surface Pressure Measurementsmentioning
confidence: 84%